An Ignored Wind Generates More Electricity: A Solar Updraft Tower to a Wind Solar Tower - Koichi Watanabe; Sho Fukutomi; Yuji Ohya; Takanori Uchida (International Journal of Photoenergy)
A solar updraft tower is one of the wind power generation plants which utilizes solar energy. The purpose of this study was to ascertain whether the tower was also able to utilize crosswind energy. Wind tunnel experiments and numerical simulations were conducted simulating the crosswind. The results showed that suctioned updraft speed in the tower was proportional to the crosswind speed, and its conversion rate depended on the tower configuration. A diffuser-shaped tower with a vortex generator achieved to produce the updraft whose speed exceeded the crosswind speed. It was due to the low pressure created by the vortex atop the tower and to the diffuser effect. The crosswind utilization enables the simple power generation device to generate electricity during the night, and the hybrid utilization of renewable energies contributes to the increasing wind energy market.